2011
DOI: 10.1038/gt.2011.117
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor improves lentivirus vector gene transfer into primary mouse hepatocytes

Abstract: Partial resistance of primary mouse hepatocytes to lentiviral (LV) vector transduction poses a challenge for ex vivo gene therapy protocols in models of monogenetic liver disease. We thus sought to optimize ex vivo LV gene transfer while preserving the hepatocyte integrity for subsequent transplantation into recipient animals. We found that culture media supplemented with epidermal growth factor (EGF) and, to a lesser extent, hepatocyte growth factor (HGF) markedly improved transduction efficacy at various mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…Primary mouse hepatocytes (PMHs) were isolated from BALB/cJ and/or C57BL/6J mice by a modified 2-step Liberase perfusion (21,22). Briefly, mice were anesthetized using ketamine (Albrecht) and Rompun (Bayer).…”
Section: Methodsmentioning
confidence: 99%
“…Primary mouse hepatocytes (PMHs) were isolated from BALB/cJ and/or C57BL/6J mice by a modified 2-step Liberase perfusion (21,22). Briefly, mice were anesthetized using ketamine (Albrecht) and Rompun (Bayer).…”
Section: Methodsmentioning
confidence: 99%
“…Vector-derived copy numbers were determined by real-time PCR as described previously (18,19). A total of 100 ng/2 ml genomic DNA prepared from the above step were added to the 13-ml RQ-PCR mix containing 7.5 ml SYBRTaq mix with 1 ml primer mix for woodchuck hepatitis virus posttranscriptional regulatory element, 59-GAGGAGTTGTGGCCCGTTGT-39 (forward), and 59-TGACA-GGTGGTGGCAATGCC-39 (reverse); or polypyrimidine tract binding protein 2, 59-TCTCCATTCCCTATGTTCATGC-39 (forward), and 59-GTTCCCGCAGAATGGTGAGGTG-39 (reverse), adjusting the volume to 13 ml with PCR-grade nuclease-free water.…”
Section: Real-time Pcr For Analyses Of Lentiviral Vector Copies In Timentioning
confidence: 99%
“…3B) but were actually present at low levels; the 10 other samples showed a low correlation (r = 0.138, p = 0.6687) with qPCR data. Furthermore, this experiment showed that in a set of insertions in which we expected no or little clonal expansion because these hepatocytes failed to divide in vitro (Rothe et al, 2012), we did find clones with associated high numbers of reads (Fig. 3A), which would have led us to the erroneous conclusion that expansion of several individual clones did occur.…”
Section: Lm-pcr: 454 Pyrosequencing Sensitivity Compared With Site-spmentioning
confidence: 90%